Effect of mycorrhization and water stress on morphological parameters, concentration of phenolic compounds and antioxidant capacity of methanolic extract of Lupinus albus - Abaid, Siham; Bachir Bouiadjra, Salah Eddine; Toumi-Benali, Fawzia; Dahlia, Fatima; Bouteldja, Rachida; Aggad, Hebib (Environmental and Experimental Biology, 2021)
Secondary metabolites and mycorrhizal symbiosis play important roles in the adaptation of plants to environmental conditions, but mycorrhizal symbiosis favours also accumulation of secondary metabolites. Our objective was to study effect of interaction between mycorrhization and water deficiency on morphological parameters, phenolic compound concentration in Lupinus albus and to perform an evaluation of the antioxidant potential of methanolic extract of this plant. Plants of L. albus were subjected to three levels of water defficiency (80, 50 and 30% of field capacity). Half of the plants in each treatment were inoculated with arbuscular mycorrhizal fungi. Total concentrations of polyphenols, flavonoids, and condensed tannins were measured, and antioxidant potential of methanolic extracts from leaves and roots of white lupin plants was evaluated. In general, mycorrhizal plants of L. albus had better growth indices in all watering regimes in comparison to non-mycorrhizal plants. The concentrations of phenolic compounds were maximal in the leaf extracts from L. albus plants inoculated with arbuscular mycorrhizal fungi grown under 30% of field capacity water regime, and in root extract of non-inoculated plants grown under 30% of field capacity. Methanolic extracts of all plants showed good antioxidant activity, with higher values in mycorrhizal drought-stressed plants.